PRIORITY DIRECTIONS OF YOUTH POLICY IN VOCATIONAL EDUCATION INSTITUTIONS IN THE SUBJECTS OF RUSSIAN FEDERATION - A. Nikolaeva; A. Bokova (Вестник университета)
This article describes the features and priority areas of regional youth policy as an example of Stavropol Territory and Moscow. The theoretical basis of the work is amounted to legal sources that regulate the state youth policy, youth policy in the Stavropol region and Moscow, as well as the analysis of publications of researchers, considering the subject. Based on the analysis the authors offers recommendations to improve organization of the youth work in the territory of the region under study.